Marine Ranching Engineering Collaborative Innovation from the Perspective of Ecological Environment - Wan, Xiaole; Zhang, Guixian; Li, Qianqian (Journal of Ocean University of China, 2023)
As a resource development model with both economic and ecological functions, the environmental friendliness of marine ranching products meets the environmental needs of consumers. However, the lack of technological innovation ability limits the development of marine ranching. Therefore, this research builds a marine ranching collaborative innovation system with multi-agent participation. Evolutionary game theory is used to analyze strategic choices of all parties and the conditions of system equilibrium, and numerical simulation is used to analyze the effect of relevant factors. This paper integrates the benefits from the improvement of environmental friendliness into the payoff matrix, and explains the significance of collaborative innovation to the development of marine ranching from the perspective of ecological environment. The results showed: the participation willingness of marine ranching enterprises is positively related to open innovation subject, while the participation willingness of the other two parties is negatively related to the government; The incentive effect of collaboration is negatively correlated with the government’s will, positively correlated with the other two parties; The incentive effect of government subsidies positively affects the willingness of the three parties to participate. Finally, suggestions are provided for each participant to maintain the strategic choice of marine ranching collaborative innovation system.